Assessment of muscle fatigability using isometric repetitive handgrip strength in frail older adults. A cross-sectional study - Ali Kapan; Milos Ristic; Anna Leser; Richard Felsinger; Thomas Waldhoer (Journal of Translational Medicine, 2025)
Abstract Background Fatigue has a significant impact on physical performance and quality of life in older adults, but is subjectively assessed in the Fried phenotype, so early deterioration may be overlooked. This study explores whether repetitive handgrip strength (HGS) provides an objective method of differentiating levels of frailty by comparing fatigue and recovery ratios with subjective measures and their correlations with frailty indicators. Methods Participants (n = 217) were included based on mobility and cognitive function (MMSE > 17), with exclusions for neuromuscular disease or hand injury. The protocol consisted of two 10-maximal grip assessments one hour apart, calculating fatigue ratios 1 and 2 (maximum/mean force) at each session and recovery ratios between sessions. Logistic regression analysed associations between Fried’s criteria components (Unintentional Weight Loss, Exhaustion Single Question, Multidimensional Fatigue Inventory (MFI), Short Physical Performance Battery (SPPB), Physical Activity Scale for the Elderly (PASE), standard Maximum HGS, Fatigue Ratio, and Recovery Ratio). Results Among the participants (58 non-frail, 68 pre-frail, 91 frail; ages 74.7, 79.4, 83.8 years), significant differences were found for Fatigue Ratio 1 of 1.12 (non-frail), 1.23 (pre-frail), 1.40 (frail), Fatigue Ratio 2 of 1.12, 1.21, 1.45, and Recovery Ratio of 1.03, 1.01, 0.90, respectively. Fatigue Ratios 1, 2 and Recovery correlated more strongly with frailty status (r = 0.67, 0.69, -0.68) than MFI (r = 0.50), standard maximum HGS (r = -0.51) or a single fatigue question (r = 0.21). In logistic regression for predicting fatigue (MFI), Fatigue Ratio (OR = 1.51, p < 0.001) and Recovery Ratio (OR = 0.83, p = 0.022) were stronger predictors than single-question fatigue (OR = 1.15, p = 0.047) and maximum HGS. For predicting frailty, physical performance (SPPB) was the strongest predictor (OR = 0.72, p < 0.001), followed by Fatigue Ratio 1 (OR = 1.28, p < 0.001), with a higher Recovery Ratio reducing frailty risk (OR = 0.86, p = 0.050). Conclusion The repetitive HGS protocol is equivalent to the SPPB in assessing frailty and outperforms standard HGS and subjective fatigue measures. This objective method supports the identification of frailty by measuring strength, fatigue resistance and recovery capacity.